How do you simplify #(y ^ { 3} z ^ { - 1} ) ( \frac { x y ^ { - 2} } { 3z ^ { - 2} } ) ^ { 2}#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Feb 6, 2018

Answer:

#=(x^2z^3)/(9y)#

Explanation:

Simplify:
#(y^3z^-1)((xy^-2)/(3z^-2))^2#
#=y^3(1/z)(xy^-2)^2/(3z^-2)^2#
#=y^3/z(x^2y^-4)/(3^2z^-4)#
#=(y^(3-4)x^2)/(9z^(1-4))#
#=(y^-1x^2)/(9z^-3)#
#=1/y(1/9)x^2z^3#
#=(x^2z^3)/(9y)#

Was this helpful? Let the contributor know!
1500